A whole-body dual-modality radionuclide-optical strategy for pre-clinical imaging of metastasis and heterogeneous treatment response in different microenvironments - Fruhwirth, Gilbert O. (J Nucl Med, 2014)
Imaging spontaneous cancer cell metastasis or heterogeneous tumor responses to drug treatment in vivo is difficult to achieve. The goal was to develop a new highly sensitive and reliable pre-clinical longitudinal in vivo imaging model for this purpose thereby facilitating discovery and validation of anticancer therapies or molecular imaging agents. METHODS: The strategy is based on breast cancer cells stably expressing the human sodium iodide symporter (NIS) fused to a red fluorescent protein, thereby permitting radionuclide and fluorescence imaging. Using whole-body nanoSPECT/CT with (99m)TcO(4)(-) we followed primary tumor growth and spontaneous metastasis in the presence and absence of etoposide treatment. NIS imaging was used to classify organs as small as individual lymph nodes (LN) to be positive or negative for metastasis and results were confirmed by confocal fluorescence microscopy. Etoposide treatment efficacy was proven by ex vivo anti-caspase 3 staining and fluorescence microscopy. RESULTS: In this pre-clinical model, we found the NIS imaging strategy to out-perform state-of-the-art FDG imaging in its ability to detect small tumors (18.5-fold better Tumour:Blood ratio) and metastases (LN: 3.6-fold) due to improved contrast in organs close to metastatic sites (12- and 8.5-fold lower SUV in heart and kidney, respectively). We applied the model to assess the treatment response to the neo-adjuvant etoposide and found a consistent and reliable improvement in spontaneous metastasis detection. Importantly, we also found that tumor cells in different microenvironments responded in a heterogeneous manner to etoposide treatment, which could only be determined by the NIS-based strategy and not by FDG imaging. CONCLUSIONS: We developed a new strategy for pre-clinical longitudinal in vivo cancer cell tracking with greater sensitivity and reliability than FDG PET, and applied it to track spontaneous and distant metastasis in the presence or absence of genotoxic stress therapy. Importantly, the model provides sufficient sensitivity and dynamic range to permit the reliable assessment of heterogeneous treatment responses in various microenvironments.